Qishas Dan Diyat Menurut Perspektif Hukum Pidana Islam - Norhalifah; Rainah; Lahmudinur (PT. Pustaka Andil Lestari, 2025)
This study examines the concepts of qishas and diyat as fundamental instruments in Islamic criminal law designed to protect human life and uphold justice through balanced and measurable legal mechanisms (Introduction). The research employs a juridical-normative approach by analyzing Qur’anic texts, hadith, classical fiqh literature, and contemporary legal scholarship to explore the normative foundations and legal principles governing qishas and diyat (Methods). The findings reveal that qishas functions as a proportional retributive measure intended to prevent uncontrolled retaliation and maintain social order, while diyat serves as a compensatory mechanism emphasizing reconciliation, social restoration, and the promotion of forgiveness (Results). Further discussion shows that the application of both concepts requires strict legal criteria, including clarity of the offender’s identity, the absence of doubt, and the full authority of the victim’s family in determining the form of legal settlement; moreover, the principles embedded in qishas and diyat strongly align with modern restorative justice models that prioritize dialogue, compensation, and healing over punitive sanctions (Discussion). Thus, qishas and diyat offer valuable insights for the humanization and reform of contemporary criminal law systems.